Azithromycin susceptibility testing for salmonella enterica isolates: Comparing disk diffusion results with MIC gradient strips - Sultan, Aqib; Safdar , Nida; Malik, Nasrullah; Nizamuddin, Summaiya (Infectious Diseases Journal of Pakistan, 2023)
Background: Enteric fever remains an imperative public health problem in developing countries. After the emergence of cephalosporin resistance in Salmonella enterica subsp. enterica serovar Typhi, azithromycin is increasingly being used for oral treatment of enteric fever. Reports of sporadic azithromycin resistance have been reported across the country, additionally, misuse of azithromycin during the COVID-19 pandemic has concerns regarding emerging azithromycin resistance. This study evaluated the reliability of the disc diffusion method as a screening test for detecting azithromycin resistance by comparing it with the minimum inhibitory concentrations (MIC) gradient strip results, in 231 typhoidal salmonellae. Material and Methods: This prospective study was conducted in the Section of microbiology of the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore from March 2022 to March 2023. Isolates recovered from blood cultures of patients, suffering from enteric fever were selected. Azithromycin susceptibility testing was performed both by disk diffusion and as well as gradient strips and their results were compared. Results: Among typhoidal salmonellae, a significant portion consisted of extensively drug resistant Salmonella Typhi (61.9%). Only one XDR S. Typhi was found to be resistant to azithromycin both by disk diffusion method and MIC gradient strip method, with a MIC value of 64µg/ml. The study found no discrepancy between the disk diffusion and gradient strip methods. Conclusion: The current study found no discordance between disk diffusion and gradient strip test methods for evaluating azithromycin susceptibility among typhoidal salmonellae. Keywords: Azithromycin, disk diffusion testing, enteric fever, Minimum inhibitory concentration, Salmonella Typhi